Odyssey Self Reflection - Guitar / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif
The string instrumental form of a guitar had inspired me to create artworks which consisted of drawing, painting, printmaking and sculpture. I am very interested in the contemporary art, and my artwork ideas were heavily influenced from the many designs of that era. The classic formof a guitar was the highlight of the elements and principles ofmy artworks. I applied the ready-made materials for mysculpture such as wood and I used mixed techniques for my printmaking artwork namely intaglio and stencil.